2021
DOI: 10.25259/ijdvl_114_20
|View full text |Cite
|
Sign up to set email alerts
|

Lucio phenomenon in a patient of lepromatous leprosy from India

Abstract: This is an open-access article distributed under the terms of the Creative Commons Attribution-Non Commercial-Share Alike 4.0 License, which allows others to remix, tweak, and build upon the work non-commercially, as long as the author is credited and the new creations are licensed under the identical terms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 12 publications
0
2
0
3
Order By: Relevance
“…Very few cases have been reported from India. 1 Its precise aetiopathogenesis has not been elucidated. It is believed that the unhindered multiplication of lepra bacilli in an anergic background leads to their diffuse infiltration.…”
Section: Discussionmentioning
confidence: 99%
“…Very few cases have been reported from India. 1 Its precise aetiopathogenesis has not been elucidated. It is believed that the unhindered multiplication of lepra bacilli in an anergic background leads to their diffuse infiltration.…”
Section: Discussionmentioning
confidence: 99%
“…Histopathology of Vasculonecrotic erythema nodosum usually showed necrotizing vasculitis with neutrophilic infiltrate, but no involvement of medium sized vessels, thrombosis or endothelial infiltration by acidfast bacilli. 4 The study by Bernard and colleagues showed how to distinguish the lucio phenomenon from the necrotic erythema nodosum. 5 The lucio phenomenon is a reactive state resulting from spontaneous multiplication of lepra bacilli leading to diffuse organ involvement in a dormant setting.…”
Section: Discussionmentioning
confidence: 99%
“…Para ahli melaporkan bahwa penegakan diagnosis dan terapi yang tepat sejak dini terapi dapat meningkatkan prognosis dan perkembangan lesi klinis. 12,13 Prognosis penyakit ini bervariasi, beberapa peneliti menyebutkan bahwa komplikasi sepsis dan gangguan koagulasi dapat menyebabkan kematian. 13 Pada kasus ini, hasil kultur luka ditemukan pertumbuhan kuman Pseudomonas luteola dan Klebsiella pneumoniae, ini menimbulkan kecurigaan terjadinya infeksi sekunder yang dapat berkembang menjadi necrotizing fasciitis.…”
Section: Pembahasanunclassified
“…12,13 Prognosis penyakit ini bervariasi, beberapa peneliti menyebutkan bahwa komplikasi sepsis dan gangguan koagulasi dapat menyebabkan kematian. 13 Pada kasus ini, hasil kultur luka ditemukan pertumbuhan kuman Pseudomonas luteola dan Klebsiella pneumoniae, ini menimbulkan kecurigaan terjadinya infeksi sekunder yang dapat berkembang menjadi necrotizing fasciitis. Namun hasil penghitungan nilai LRINEC adalah dua, serta tidak didapatkan area nekrotik luas yang mencapai subkutan pada gambaran histopatologi dapat menyingkirkan diagnosis banding ini.…”
Section: Pembahasanunclassified
See 1 more Smart Citation